Strategy change and wealth accumulation in financial markets - Zhang, Yu (2016)
This thesis studies investors' strategy change behavior and how such behavior affects investors' wealth accumulation by financial investments. Other issues relate to financial markets, such as the performance of strategies, fundamental value, the formation and burst of bubbles, stock cycles, are also investigated. Heterogeneous agent modeling is used as the main methodology. Chapter 1 introduces the history and latest development of heterogeneous agent models and describes the motivation of this thesis. Chapter 2 studies investors' strategy change frequency and their wealth accumulation by financial investments. Artificial investors are put into a stock market. They trade S&P 500 index following common strategies in practice. Driven by past performance of strategies, investors change strategy at different frequencies. There are special regions where investors who change strategy more often end up with less final wealth under diverse market trends. A detailed decomposition of wealth accumulation via financial investment shows the dependence of wealth on investors' past transactions. Chapter 3 introduces a new heterogeneity, that is, agents' propensity of strategy switching, to the heterogeneous agent model. Numerical analysis shows that agents with higher propensity adopt the better strategy more often but end up with less final wealth. As this parameter, investors' propensity of strategy switching, can be interpreted as the speed of adaptive learning, the economic meaning that fast adaptive learning can hurt wealth accumulation seems counter-intuitive. Further investigation reveals the inconsistency between investors' strategy switching and their wealth accumulation, which causes the counter-intuitive phenomenon. Wealth accumulation relies heavily on the position of risky asset an investor holds and its corresponding market value, rather than on the profit earned in the latest trading. Chapter 4 improves the heterogeneous agent model built in Chapter 3. In Chapter 3, the fundamental value of the stock is exogenous. In Chapter 4, the fundamental value is endogenously determined by a production process. This distinguishes my work from other models with endogenous fundamental, as almost all of them take the New-Keynesian approach which relates the fundamental to the demand side of the real economy. More realistic issues like constraints on budget, short-sale and liquidity are covered. Under a nonlinear price dynamics and all constraints faced by investors, the prices of risky asset show cyclical motions. Stock bubbles form and burst along stock cycles. The formation of bubbles hurt the real economy by drawing resource from future production. Though in general chartists are less wealthy than fundamentalists, they have a significant impact on the stock price. Chapter 5 summarizes this thesis and points out future research directions.